2021
DOI: 10.3390/ph14040369
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone, as a Novel Therapeutic Candidate of Cancers

Abstract: To date, natural products are widely used as pharmaceutical agents for many human diseases and cancers. One of the most popular natural products that have been studied for anticancer properties is thymoquinone (TQ). As a bioactive compound of Nigella sativa, TQ has shown anticancer activities through the inhibition of cell proliferation, migration, and invasion. The anticancer efficacy of TQ is being investigated in several human cancers such as pancreatic cancer, breast cancer, colon cancer, hepatic cancer, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 126 publications
1
55
0
Order By: Relevance
“…Thymoquinone has been shown to have anticancer properties against several types of leukaemia by inducing DNA damage and G0/G1 cell cycle arrest [30,52]. In line with the literature, this study found that TQ considerably blocked cell cycle transition in MV4-11 cells at the G0/G1 phase in a time-and dose-dependent manner (Figure 2A,B).…”
Section: Discussionsupporting
confidence: 88%
“…Thymoquinone has been shown to have anticancer properties against several types of leukaemia by inducing DNA damage and G0/G1 cell cycle arrest [30,52]. In line with the literature, this study found that TQ considerably blocked cell cycle transition in MV4-11 cells at the G0/G1 phase in a time-and dose-dependent manner (Figure 2A,B).…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, there is an urgent need for a novel and more efficient treatment for such malignancies. Accumulated evidence based on in vivo and in vitro studies indicated the anti-cancer properties of compounds obtained from natural products [ 12 ]. Thymoquinone (TQ), chemically known as 2-methyl-5-isopropyl-1,4-benzoquinone, is an active phytochemical compound of Nigella sativa (black seeds) that has shown anti-proliferative, pro-apoptotic, and anti-metastatic properties on numerous cancer cell types including leukemia cells [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been subject of repeated studies evaluating its chemopreventive and anticancer effects [ 209 ]. Thereby, thymoquinone was targeting a variety of kinases and additionally showed effectiveness in murine tumor models [ 210 , 211 ]. In order to evaluate its antimyeloma potential, the compound was investigated for its antiproliferative effect on U266 and RPMI8226 cells, with IC 50 values below 10 µM after 12 h of incubation [ 208 ].…”
Section: Resultsmentioning
confidence: 99%